2019
DOI: 10.5334/aogh.2570
|View full text |Cite
|
Sign up to set email alerts
|

<sup>13</sup>C-Urea Breath Test Accuracy for <i>Helicobacter pylori</i> Infection in the Asian Population: A Meta-Analysis

Abstract: Background: Helicobacter pylori (H. pylori) infection is known to be associated with peptic ulcer and gastric cancer. Detection of H. pylori infection is a significant part of peptic ulcer and gastric cancer prevention and management. 13 C-urea breath test (UBT) provides a good option for the pathogen detection due to its accuracy and safety. Objective: This review aims to evaluate the 13 C-UBT diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 29 publications
1
12
0
3
Order By: Relevance
“…The high accuracy of 13 C-UBT was also confirmed in a meta-analysis, including 15 studies performed in Asia. The sensitivity and specificity results were excellent, notwithstanding the heterogeneity observed across all studies [ 54 ].…”
Section: Non-invasive Testsmentioning
confidence: 99%
“…The high accuracy of 13 C-UBT was also confirmed in a meta-analysis, including 15 studies performed in Asia. The sensitivity and specificity results were excellent, notwithstanding the heterogeneity observed across all studies [ 54 ].…”
Section: Non-invasive Testsmentioning
confidence: 99%
“…There might be a possibility that false-negative post-WMT UBT results were obtained in some patients. However, 13 C-UBT has been used in clinical practice as a standard method to determine H. pylori status after H. pylori eradication therapy, due to its high sensitivity and specificity [ 42 44 ]. Thus, it is unlikely that the false-negative results 13 C-UBT occurred in nearly 30% of cases after WMT.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a meta‐analysis by Abd Rahim et al, reported the different 13 C‐UBT accuracy studies conducted in Asia 32 . In total, 15 protocols were referenced and analysed by the authors.…”
Section: Non‐invasive Testsmentioning
confidence: 99%